An In Vivo Inflammatory Loop Potentiates KRAS Blockade - Kristina A. M. Arendt; Giannoula Ntaliarda; Vasileios Armenis; Danai Kati; Christin Henning; Georgia A. Giotopoulou; Mario A. A. Pepe; Laura V. Klotz; Anne-Sophie Lamort; Rudolf A. Hatz; Sebastian Kobold; Andrea C. Schamberger; et al. (Biomedicines, 2022)
KRAS (KRAS proto-oncogene, GTPase) inhibitors perform less well than other targeted drugs in vitro and fail clinical trials. To investigate a possible reason for this, we treated human and murine tumor cells with KRAS inhibitors deltarasin (targeting phosphodiesterase-δ), cysmethynil (targeting isoprenylcysteine carboxylmethyltransferase), and AA12 (targeting KRASG12C), and silenced/overexpressed mutant KRAS using custom-designed vectors. We showed that KRAS-mutant tumor cells exclusively respond to KRAS blockade in vivo, because the oncogene co-opts host myeloid cells via a C-C-motif chemokine ligand 2 (CCL2)/interleukin-1 beta (IL-1β)-mediated signaling loop for sustained tumorigenicity. Indeed, KRAS-mutant tumors did not respond to deltarasin in C-C motif chemokine receptor 2 (Ccr2) and Il1b gene-deficient mice, but were deltarasin-sensitive in wild-type and Ccr2-deficient mice adoptively transplanted with wild-type murine bone marrow. A KRAS-dependent pro-inflammatory transcriptome was prominent in human cancers with high KRAS mutation prevalence and poor predicted survival. Our findings support that in vitro cellular systems are suboptimal for anti-KRAS drug screens, as these drugs function to suppress interleukin-1 receptor 1 (IL1R1) expression and myeloid IL-1β-delivered pro-growth effects in vivo. Moreover, the findings support that IL-1β blockade might be suitable for therapy for KRAS-mutant cancers.